2011
DOI: 10.5114/aoms.2011.23418
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Firmicutes and Bacteroidetes in gut microbiota in obese and normal weight Egyptian children and adults

Abstract: IntroductionObesity and associated metabolic disorders are a worldwide epidemic. Recent evidence suggests that the microbial community in the human intestine may play an important role in the pathogenesis of obesity. The aim of this study was to assess the differences in the composition of the intestinal microbiota between obese and normal weight Egyptian children and adults.Material and methodsThe study included 79 subjects among whom 51 were obese (23 children and 28 adults), and 28 were subjects of normal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
133
5
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(153 citation statements)
references
References 33 publications
7
133
5
8
Order By: Relevance
“…A recent meta-analysis concluded that there were no statistically significant differences across multiple studies in the Firmicutes/Bacteroidetes ratio between obese and normal-weight adults (Walters et al, 2014). In agreement with this meta-analysis, some pediatric studies have Ismail et al, 2011;Payne et al, 2011). Although in our study the Firmicutes/Bacteroidetes ratio was significantly elevated in obese individuals, we observed large variation in the ratio, particularly within the obese group.…”
Section: Discussioncontrasting
confidence: 38%
“…A recent meta-analysis concluded that there were no statistically significant differences across multiple studies in the Firmicutes/Bacteroidetes ratio between obese and normal-weight adults (Walters et al, 2014). In agreement with this meta-analysis, some pediatric studies have Ismail et al, 2011;Payne et al, 2011). Although in our study the Firmicutes/Bacteroidetes ratio was significantly elevated in obese individuals, we observed large variation in the ratio, particularly within the obese group.…”
Section: Discussioncontrasting
confidence: 38%
“…A recent meta‐analysis concluded that there were no statistically significant differences across multiple studies in the Firmicutes / Bacteroidetes ratio between obese and normal‐weight adults (Walters et al ., 2014). In agreement with this meta‐analysis, some pediatric studies have found an increase in Firmicutes and a decrease in Bacteroidetes (Bervoets et al ., 2013; Ferrer et al ., 2013) while others have not (Abdallah Ismail et al ., 2011; Payne et al ., 2011). Although in our study the Firmicutes / Bacteroidetes ratio was significantly elevated in obese individuals, we observed large variation in the ratio, particularly within the obese group.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Similar to our results, an increase in the proportion of these phyla was observed in European and African OW/W children compared to NW children. 9,10,20 However, several studies in adults have found an increase of Bacteroidetes, 21,22 less proportion of Firmicutes, unaltered Bacteroidetes ratio, 23 or no differences in the proportions between these two phyla with the obesity degree. 24,25 In the present study, we found a high relation of Firmicutes/Bacteroidetes in obese children which is consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…6,8 Recent studies including ours have shown similar findings in obese children. [9][10][11] The risk of OW/O is associated with the high abundance of Firmicutes that is dependent on the high consumption of simple carbohydrates and saturated fats, and low ingestion of micronutrients and fiber. Pro-inflammatory cytokines are known to be increased in serum of subjects with OW/O; particularly, IL-6 and TNF-α (which are also referred as adipokines released by adipocytes), that favor insulin resistance and hypertension.…”
Section: Introductionmentioning
confidence: 99%